Penilaian Alat Hasil Belajar Untuk Siswa Sekolah Dasar SDN Sindangsari 1 Desa Sindangsari - Ramadhani, Annisa Nurul; Ardiansyah, Riyo Gilang; Latifah, Ummi (Lembaga Yasin AlSys, 2022)
This paper discusses learning outcomes for elementary school students including aspects of knowledge, attitudes, and skills through improving learning outcomes by educators, assessment of learning outcomes by education units. From the results of the study, it can be said that it was carried out by educators and educators who with various techniques and procedures knew authentic in the realm of knowledge, attitudes and skills. For the final assessment taken using the Assessment method, the assessment is taken from several stages including: daily tests, mid-semester assessment skills, final semester assessments, as well as projects and assignments given. All the scores from above are then combined and the final score will be procedurized for learning.